Apie specialiųjų hiperplokštuminių elementų erdvių geometriją - Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2007)
In this paper analystes metric space of hyperplane elemente with special metric. Is prowed, that in such spaces intrinsic almost complex and almost product structures exists, criteria of its integrability and associated connections established.